PENGARUH SELF-CONFIDENCE TERHADAP HASIL BELAJAR SPEAKING PADA MAHASISWA STIKES HAMZAR SEMESTER IV - Suhaemi Suhaemi; Bq. Fina Farlina (Pusat Riset dan Inovasi Nasional, 2021)
One of the skills that must be mastered from the four skills is speaking. Where speaking ability aims to enable learners to develop speaking proficiency effectively. However, the ability to speak English is still a difficult thing. It is also coupled with the level of confidence that learners have. This study aims to determine the influence of self-confidence on the learning outcomes of speaking on STIKes Hamzar students in semester IV. Method: This research is quantitative descriptive research. The population in this study amounted to 26 The sampling technique used was total sampling with a sample size of 26 students. The instrument used is a questionnaire and the value of English learning outcomes. Data analysis was carried out on the results of questionnaires and student learning results which were then carried out correlation tests. Results: The level of self-confidence of Semester IV students most of them are in the medium category. This is evidenced by the percentage of self-confidence of 73%. Self-confidence influences the learning outcomes of English in IV semester Nursing. This is shown by the correlation test between Self-Confidence and English Speaking learning outcomes with a significance level of P = 0.000 (p <0.05).